Capture of 3‐Amino‐4‐oxycyanofurazan and Characterization of Isoxazole Product. (14th February 2013) - Luo, Yifen; Wang, Bozhou; Zhang, Guofang; Zhou, Yanshui; Lian, Peng
<x xml:space="preserve">Abstract</x> 1, 3‐Dipolar cycloaddition reaction between nitrile oxide and alkyne was used to capture 3‐amino‐4‐oxycyanofurazan (AOCF), which was considered as the key intermediate during the synthesis of 3, 4‐bis(4‐aminofurazano‐3‐yl)furoxan (DATF) from 3‐amino‐4‐chloroximinofurazan. The isolated isoxazoles from the reaction afforded evidences for the existence of AOCF. The structures of the isoxazoles were characterized by IR, 1H NMR, 13C NMR, MS, and elemental analysis. In addition, single crystal X‐ray diffraction of one isoxazole was obtained.